Aphthous Ulcer–A Rare Effect of Losartan - Jain, Ayaana; Deshpande, Anushree (Indian Journal of Pharmacy Practice)
The most common type of oral mucosa ulcer is an aphthous ulcer, which manifests as a painful sore on the mucous membranes of the mouth or genitalia.1 We describe a case of a male patient who was admitted to the hospital due to anorexia, generalized weakness, weight loss, trouble opening the mouth, glossitis, and aphthous ulcers. The patient’s history and recent medication history indicated that the symptoms began to appear when losartan for hypertension was started. The use of losartan was stopped, and the patient’s glossitis and mouth ulcers were treated symptomatically. After 15 days of drug withdrawal, the symptoms began to subside. According to the WHO and Naranjo ADR assessment, Losartan had a “possible” connection with the oral toxicity seen in this patient.
Keywords: Aphthous ulcers; Mucous membrane; Glossitis; Losartan; ARBs; FDA